PENGARUH KONFLIK PERAN, KETIDAKJELASAN PERAN, KELEBIHAN PERAN, KETEGANGAN PEKERJAAN, LINGKUNGAN KERJA INDIVIDU DAN PEKERJAAN ADMINISTRATIF YANG BERLEBIH TERHADAP BURNOUT (STUDI EMPIRIS DI KAP SEMARANG) - Ignatius Sendy Wiratmoko, 13.05.52.0036; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2017)
Stress can be positive or negative impact. Stress at a certain level it can motivate a person to improve performance and get the job done. The type of stress that negatively or dysfunctional (distress) on the performance referred to by the term burnout This study aimed to examine the effect of role conflict, role ambiguity, role overload, tension, work environment of individual and excessive administrative work against burnout. The sampling technique used purposive sampling with judgment sampling, the sampling is not random sample is selected based on certain considerations. The type of data in this study are primary data using questionnaires were processed as many as 36. The tool used is multiple linear regression. This study provides results that role conflict, role ambiguity, role overload and individual work environment positive effect on burnout. While the tensions of work and excessive administrative work does not affect the burnout.Keywords:Â Role Conflict, Role Ambiguity, Role Overload, Job Tension, Individual Work Environments, Excessive Administrative Work, Burnout